СРАВНИТЕЛЬНАЯ ОЦЕНКА ФИЗИЧЕСКОГО РАЗВИТИЯ СПОРТСМЕНОВ ИГРОВЫХ ВИДОВ спорта - Ядгаров, Б.Ж.; Утепбергенов, А.К. (SCIENCE and SOCIETY, 2018)
In the article we present a comparative analysis of level of physical development of sportsmen specializing in volleyball, basketball and football. In has been stated that basketball and volleyball players show more similarity in a considerable number of morphological factors comparatively with football players.
Keywords: training loading; gain of physical preparation; physical development; somatotype; dermothoglifics